Method for regulating and controlling aperture of solid nanopore array template
Through magnetron sputtering method and chemical etching technology, the diameter of solid-state nanopore arrays is continuously adjustable, solving the problem of difficult nanopore diameters in the existing technology, improving the efficiency and sensitivity of biomolecular detection, and simplifying the Preparation process.
Patent Information
- Application Number
- CN202411390845.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The prior art is difficult to prepare solid-state nanopore arrays with continuous adjustable diameters, limiting the detection capability and detection efficiency of biological molecules with smaller sizes.
The metal nanowire array-ceramic composite film was prepared by magnetron sputtering method. Through the regulation of chemical etching fluids A and B, fine-tuning of the nanopore diameter within the range of 0.1-1.2 nm is achieved, which simplifies the preparation process and avoids high energy. The complexity of electron beam and lithography.
A solid-state nanopore array with large-area preparation and precise regulation of nanopore diameters is realized, which improves the sensitivity and resolution of biomolecular detection, and reduces the preparation cost and operational complexity.
Smart Images

Figure CN119144928A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and in particular to a method for regulating pore diameters using a solid-state nanopore array template. Background Art
[0002] Solid-state nanopores have important applications in biomolecule detection, especially in DNA and RNA sequencing. They also have broad prospects in potential applications such as nanofiltration, supercapacitors, energy conversion and storage. In the process of biomolecule detection, the nanopore is embedded in a thin film and immersed in an electrolyte solution. The electric field on both sides will drive the molecules to pass through the nanopore and generate corresponding ion current signal fluctuations. The size, structure and other information of the biomolecules are determined by analyzing the current changes. For the detection of biomolecules, when the diameter of the nanopore matches the size of the target molecule (the same as or slightly larger than the molecular size), the detection results will have the characteristics of high sensitivity and high resolution.
[0003] For common biomolecules, such as DNA duplexes (diameter of about 2 nm), protein complexes (diameter of 1.5-2.5 nm), amino acid polymers (diameter of 5.5±1.1-8 nm), etc., the size difference between them is very small (sub-nanometer level). Considering the diversity and size of biomolecules, obtaining nanopores with controllable size and continuously adjustable diameter at the sub-nanometer scale is of great significance for the detection of biomolecules, single molecule detection, and gene sequencing.
[0004] In recent years, the preparation of solid-state nanopores mainly adopts local high-energy micromachining processes, such as laser beam irradiation, high-energy particle (ion) beam irradiation, high-voltage discharge, electroporation, etc. Yuan et al. (Controllable fabrication of solidstate nanopores array by electron beam shrinking. Int. J. Mach. ToolManufact., 2020, 159:103623) used focused ion beam technology to prepare nanopores with a pore size range of 41-166 nm on Si3N4 film, and then used high-energy electron beam irradiation to deposit hydrocarbon compounds on the edge of the nanopores to reduce the diameter of the nanopores. The minimum diameter of the nanopores prepared by this technology is 5.8 nm.
[0005] Liu et al. (Direct fabrication of sub-10 nm nanopores in WO3 nanosheetsusing single swift heavy ions. Nano Lett., 2023, 23:4502) used fast heavy ions to directly prepare sub-10 nm random nanopores on WO3 nanosheets. By selecting ions with different types and energies, the pore size and density of the nanopores can be controlled. However, preparation techniques such as electron beam and fast heavy ion breakdown have problems such as the need for high-energy beams in the preparation process, too few nanopores prepared at a time, and high equipment costs. And the problem with using a single solid-state nanopore for detection is that it has a more complicated and cumbersome operation process, high preparation cost, and low sequencing efficiency, which greatly limits the efficiency of molecular detection.
[0006] One of the methods to improve the detection efficiency of solid-state nanopores is to use solid-state nanopore array devices to achieve high-throughput physical sequencing. Researchers have made many new attempts in the preparation of solid-state nanopore arrays, and large-scale self-ordered solid-state nanopore films have been attempted to be prepared. The Chinese patent document with publication number CN115093948A discloses a method for resolving biological molecules and its solid-state nanopore four-hole array device. The patent uses a helium ion microscope to etch a four-nanopore array structure, the pore size of the nanopore is 5-10 nm, and the distance between the pore centers is 30-200 nm. Although this method prepares a highly regular solid-state nanopore array, its molecular detection results are limited to the detection of smaller biological molecules due to the limitation of the pore size range of the solid-state nanopores, and the invention only focuses on the further reduction of the nanopore diameter size, and does not consider the importance of continuously adjustable diameter for improving the resolution of molecular detection.
[0007] Therefore, it is necessary to explore a method for preparing a solid-state nanopore array structure with a continuously adjustable diameter and further improve the resolution, sensitivity and testing efficiency of solid-state nanopores for biological molecules in order to realize the widespread application of solid-state nanopores in biological detection (high-throughput detection), gene sequencing (high-throughput sequencing) and other fields. Summary of the invention
[0008] The present invention aims to solve the problem that the diameter of nanopores is difficult to micro-control and is not suitable for the detection of biomolecules with small size differences. A method for preparing a solid-state nanopore template that can adjust the pore size at the sub-nanometer scale is provided. The method can achieve diameter control of the nanopores in a small range of 0.1-1.2 nm. The preparation method is simple and can be prepared on a large area without the need for complex process preparation conditions such as photolithography or high-energy electron beams.
[0009] To achieve the above object, the technical solution adopted by the present invention is: A method for regulating pore size of a solid-state nanopore array template comprises the steps of: Step 1, ultrasonic cleaning and plasma treatment of the substrate; Step 2, using a metal target and a ceramic target as co-sputtering targets, magnetron sputtering co-deposit a metal nanowire array-ceramic composite film on a substrate; Step 3, immersing the composite material in a chemical etching solution A, etching and then washing to obtain a solid nanopore array template; Step 4, immersing the solid nanopore array template in a chemical etching solution B at 15-35° C. for etching for 1-15 min to adjust the pore size, and washing to obtain the solid nanopore array template after pore size adjustment; The pore size regulation refers to the change of the diameter of the nanopores in the solid-state nanopore array template to 0.1-1.2 nm; The chemical etching solution A is an aqueous solution of NH3·H2O and / or H2O2, and the molar fraction of the solute in the aqueous solution is 0.3-1 mol / L; The chemical etching solution B is an aqueous solution of one or more of NaOH, KOH, HCl, and H2SO4, and the molar fraction of the solute in the aqueous solution is 0.01-1 mol / L.
[0010] The present invention adopts the method of magnetron sputtering to prepare a solid nanopore array on a large area, and then through controllable wet etching, chemical etching solution A is first used to completely remove the metal phase, and then the Lewis acid or Lewis base in the chemical etching solution B is used to regulate the diameter of the solid nanopore. Due to the small diameter of the nanopore, there is a strong capillary force, the etching solution in the nanopore is firmly adsorbed, and the etching solution in the hole and the etching solution in the beaker cannot flow naturally. As the reaction proceeds, the concentration of the etching solution in the hole is lower than the concentration of the etching solution in the beaker, and the pore diameter change caused by a single etching is effectively achieved by controlling the etching time. At the same time, after the rate-controlling elementary reaction occurs, as the reaction proceeds, the content of hydrolyzed silanol and siloxane in the solid nanopore increases, which slows down the reaction process to a certain extent, until the reaction is in a state of equilibrium, that is, the amount of the consumed compound is consistent with the amount of the corresponding generated compound, and a reversible equilibrium state is maintained, so that micro-regulation can be achieved in a very small diameter range.
[0011] The substrate includes one or more of a single crystal silicon wafer, a quartz glass wafer, a sapphire, a flexible PET and an Al foil; In step 1, the ultrasonic treatment includes treatment with one or more solutions of acetone, ethanol, and deionized water for 10-30 min; the plasma treatment is carried out at 5-20×10 -5 Pa deposition pressure for 5-20 min.
[0012] The diameter of the nanopores in the solid-state nanopore array template is 1-10 nm, the average spacing of the nanopores is 3-20 nm, and the array period is 6-40 nm.
[0013] The metal phase filling rate in the composite film is 5-30%, and the ceramic phase volume accounts for 70-95%.
[0014] The metal target material includes one or more of Ag target, Cu target and Al target; the ceramic target material includes one or more of Al2O3, AlN and SiO2.
[0015] Preferably, the ceramic target material is SiO2 or AlN, because Al2O3 target material has a serious slagging phenomenon during the preparation process.
[0016] In step 2, during magnetron sputtering, the sputtering power of the metal target is 10-20 W, the sputtering power of the ceramic target is 60-100 W, and the pre-deposition pressure is 5-10×10 -5 Pa.
[0017] In step 3, the etching temperature is 15-35° C., and the etching time is 1-6 h, preferably 1-2 h. The purpose of step 3 is to etch away all the metal phases. In order to completely remove the metal phase, a longer etching time is required. Since the etching solution A does not react with the ceramic matrix, this process will not affect the diameter of the nanopores.
[0018] Preferably, the etching time in step 4 is 1-5 min, preferably 3-4 min, which can achieve regulation of the nanopore diameter by about 0.1-0.5 nm, and more precise regulation.
[0019] Preferably, the solute molar concentration of the chemical etching solution A is 0.5-1 mol / L.
[0020] Preferably, the solute molar concentration of the chemical etching solution B is 0.1-1 mol / L.
[0021] The thickness of the nanopore layer in the solid-state nanopore array film is 10-300 nm.
[0022] The array template structure has super-hydrophilicity, and its infiltration solution may include any one of deionized water, NH3·H2O, NaOH solution, KOH solution, HCl solution, H2SO4 solution, and HNO3 solution.
[0023] The porosity of the solid-state nanopore array template is 7%-64%.
[0024] In some embodiments, the process further includes repeating step 4 to adjust the pore size so that the diameter of the nanopore changes by more than 1.2 nm, and the sample etching time is the cumulative etching time.
[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) In the present invention, a solid-state nanopore array template composed of a metal phase and a ceramic phase is prepared by target co-sputtering, and the nanopore diameter is effectively and controllably adjusted or controlled by Lewis acid or Lewis base to achieve sub-nanometer size regulation, which can be applied to the detection of biological macromolecules of similar sizes.
[0026] (2) The solid-state nanopore array template preparation method of the present invention is simple. Compared with traditional solid-state nanopore preparation methods, such as electron beam lithography and high-energy particle bombardment, it is conducive to integration and can be prepared and produced on a large scale, which can further improve the material preparation efficiency.
[0027] (3) The solid-state nanopore array template with adjustable pore size prepared by the present invention has a uniform pore size up and down, which is conducive to the passage of biological molecules and improves the detection efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the process of preparing the solid-state nanopore array of Example 1.
[0029] Figure 2 This is a surface SEM image of the solid-state nanopore array structure after etching away the metal phase in step 5 of Example 1.
[0030] Figure 3 This is a surface SEM image of the solid-state nanopore array structure after the nanopore diameter is enlarged by two-step etching in step 7 of Example 1.
[0031] Figure 4 a is a physical picture of a large-area sample of a metal nanowire array-ceramic composite metamaterial prepared in step 3 in Example 2, and b is a physical picture of a large-area sample of a solid-state nanopore array structure in which the metal phase is etched away in step 5.
[0032] Figure 5 3 is a graph showing the film thickness and filling rate corresponding to different etching times in Example 3.
[0033] Figure 6 This is a contact angle test diagram of the sample with a cumulative etching time of 18 min in Example 3. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0035] The raw materials used in the following specific embodiments are all purchased from the market.
[0036] Example 1 In this embodiment, a single crystal silicon wafer is used as the substrate, and the array template prepared after regulation is a solid nanopore array, with a film thickness of 108.2 nm, a nanopore diameter of 4.6 nm, and a nanopore filling rate of 35.1%. The flow diagram of the preparation method of this embodiment is shown in FIG. Figure 1 shown.
[0037] In this embodiment, the solid nanopore array template is first deposited on a substrate by magnetron sputtering of a metal nanowire array-ceramic composite metamaterial, wherein the metal is Ag and the ceramic phase is Al2O3. The metal phase in the composite layer is first etched away by continuous chemical etching to obtain a basic solid nanopore array template, and then chemical etching is continued to obtain a solid nanopore array of a target size. The specific preparation method is as follows: Step 1, placing the substrate in acetone, ethanol and deionized water in turn, ultrasonically cleaning for 15 min and drying with nitrogen, and fixing the silicon wafer on a substrate tray; Step 2: Place the tray into the deposition chamber of the magnetron sputtering equipment, with a pre-deposition pressure of 5-10×10 -5 Pa, bombarding the substrate surface with plasma for 10 min to further clean the substrate; Step 3: Under room temperature and argon atmosphere, control the co-sputtering of the metal target and the ceramic target, with the sputtering power of the metal Ag target being 12 W and the sputtering power of the ceramic Al2O3 target being 100 W, and turn on the plasma bombardment power at 20 W. After 0.8 h of deposition, turn off the target and plasma bombardment power to obtain a metal nanowire array-ceramic composite metamaterial with a metal filling rate of 21.2%;
[0038] Step 4, at room temperature, placing the substrate coated with the metal nanowire array-ceramic composite metamaterial in 1 mol / L ammonia water for etching for 2 h to obtain a solid nanopore array template; Step 5, at room temperature, the substrate after ammonia etching was cleaned with 0.5 mol / L nitric acid solution, deionized water and ethanol for 5 min respectively, and then dried with nitrogen gas; Step 6, at room temperature, the solid nanopore array template obtained after cleaning and drying is placed in a 1 mol / L NaOH etching solution for 10 min; Step 7, at room temperature, the etched silicon wafer was washed with 0.4 mol / L NaOH solution, deionized water and ethanol in sequence for 5 min, and dried with nitrogen to obtain a solid nanopore array template with a nanopore diameter of 4.6 nm; The surface morphology of the above film samples was observed and analyzed by scanning electron microscopy (SEM). Figure 2 The SEM image of the solid-state nanopore array structure obtained in step 4 in Example 1 is given. Figure 3 The solid-state nanopore array template after the pore size is enlarged obtained in step 7 in Example 1 is given.
[0039] Through optical ellipsometer measurement, effective medium theory fitting and microstructure characterization analysis, after steps 3 and 7, the thickness of the solid-state nanopore array structure changes from 110 nm to 108.2 nm, the nanopore diameter changes from 3.6±0.1 nm to 4.6±0.1 nm, and the nanopore filling rate changes from 21.2% to 35.1%, thus realizing the sub-nanometer-scale adjustable and nanoscale-controllable preparation of the solid-state nanopore array.
[0040] Example 2 In this embodiment, Al foil is selected as the substrate, the substrate size is 10 cm×10 cm, and the array template prepared after regulation is a solid-state nanopore array, the film thickness is 107.3 nm, the nanopore diameter is 4.7 nm, and the nanopore filling rate is 35.1%.
[0041] In this embodiment, the array template with solid nanopores is first deposited on a substrate by magnetron sputtering. The metal is Cu and the ceramic phase is SiO2. The metal phase in the composite layer is first etched away by continuous chemical etching to obtain a basic solid nanopore array template. Chemical etching is continued to obtain a solid nanopore array of a target size. The specific steps are as follows: Step 1, after the substrate is soaked and cleaned with ethanol and deionized water for 5 minutes, the substrate is fixed on a substrate tray; Step 2: Place the tray into the deposition chamber of the magnetron sputtering equipment, with a pre-deposition pressure of 5-10×10 -5 Pa, using plasma to bombard the substrate surface for 20 min to further clean the substrate; Step 3: Under room temperature and argon atmosphere, control the co-sputtering of the metal target and the ceramic target, with the sputtering power of the metal Cu target being 10 W and the sputtering power of the ceramic SiO2 target being 70 W. At the same time, turn on the plasma bombardment power supply at a power of 30 W. The argon gas flow rate during co-sputtering is 10 sccm, the substrate rotates at a constant speed, and after 1.5 h of deposition, turn off the target and plasma bombardment power supply to obtain a metal nanowire array-ceramic composite metamaterial with a metal filling rate of 21.2%;
[0042] Step 4, at room temperature, placing the substrate coated with the metal nanowire array-ceramic composite metamaterial in 1 mol / L H2O2, and etching for 1.8 h to obtain a solid nanopore array template; Step 5: at room temperature, the silicon wafer after nitric acid etching is cleaned with deionized water and ethanol for 5 min in sequence, and then blown dry with nitrogen; Step 6, at room temperature, the solid nanopore array template obtained after cleaning and drying is placed in a 0.1 mol / L HCl solution, and the etching time is 10 min; Step 7, at room temperature, the silicon wafer after HCl etching was cleaned with 0.05 mol / L NaOH solution, deionized water and ethanol in sequence for 5 min, and dried with nitrogen to obtain a solid nanopore array template with a pore diameter of 4.7 nm; The samples were characterized by optical ellipsometer measurement, effective medium theory fitting and microstructure analysis. Figure 4 a shows a physical picture of a large-area sample of a metal nanowire array-ceramic composite metamaterial prepared on a flexible substrate in step 3 of Example 2, Figure 4 b is the actual picture of the solid-state nanopore array template corresponding to step 5.
[0043] Through optical ellipsometer measurement and effective medium theory fitting, the thickness of the above-mentioned solid-state nanopore array structure changed from 100 nm to 107.3 nm, the nanopore diameter changed from 4±0.2 nm to 4.7±0.1 nm, and the nanopore filling rate changed from 25.9% to 35.1%, thus realizing the controllable preparation of large-area adjustable solid-state nanopore arrays.
[0044] Compared with the sample in Example 1, the nanopore diameter of the obtained solid-state nanopore sample can be controlled at the sub-nanometer scale, and the substrate of the solid-state nanopore can be applied on a flexible substrate and can be prepared on a large area.
[0045] Example 3 The metal nanowire array-ceramic composite metamaterial is plated according to the sputtering parameters and preparation process of Example 1, except that different etching times are recorded under the same experimental conditions to obtain different thicknesses and filling rates of the solid-state nanopore arrays.
[0046] Steps 1-3 are the same as those in Example 1, and step 4 is adjusted to place six samples plated with metal nanowire array-ceramic composite metamaterials in 1 mol / L ammonia water at room temperature, and undergo an etching process for 2 h to obtain six solid nanopore array templates; Step 5: at room temperature, the silicon wafer after nitric acid etching is cleaned with deionized water and ethanol for 5 min in sequence, and then blown dry with nitrogen; Step 6, at room temperature, the six solid-state nanopore array templates obtained after cleaning and drying were placed in a 0.3 mol / L HCl solution. Using the capillary effect and the reversible chemical reaction limit, the solid-state nanopores were etched for 3 min each time. During these 3 min, the three stages of rapid chemical reaction, reduced chemical reaction rate, and chemical reaction entering a state of equilibrium were experienced. Subsequently, the etching was repeated in a newly configured 0.3 mol / L HCl solution for 3 min. The cumulative etching times of the six samples were 3 min, 6 min, 9 min, 12 min, 15 min, and 18 min, respectively. Step 7, at room temperature, the silicon wafer after HCl etching was cleaned with 0.05 mol / L NaOH solution, deionized water and ethanol in sequence for 5 min, and dried with nitrogen to obtain solid nanopore array templates with different pore sizes and filling rates; The samples were measured by optical ellipsometer, effective medium theory fitting and microstructure characterization analysis. The experimental results are as follows Figure 5 As shown in Figure 2, the thickness of the solid-state nanopore array structure changes from 109.7 nm to 107.7 nm. As the etching time increases, the nanopore filling rate increases from 21.2% to 46.8%, achieving controllable preparation of the solid-state nanopore array. The contact angle measurement results of the solid-state nanopore array sample with a cumulative etching time of 18 min are shown in Figure 2. Figure 6 As shown, the contact angle is significantly less than 30°, which is super hydrophilic. Compared with the sample in Example 1, the obtained solid nanopore sample can control the nanopore diameter at the sub-nanometer scale in a single etching by adjusting the etching time, and can achieve fine-tuning of pores in a larger size through repeated etching, which has important application value for the detection of biological molecules with similar sizes.
[0047] The specific implementation methods described above have described the technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made on the principle of the present invention shall be included in the protection scope of the present invention, and the scope of protection required by the present invention shall be subject to the scope defined in the claims.
Claims
1. A method for regulating pore size of a solid-state nanopore array template, characterized in that: Includes steps: Step 1, ultrasonic cleaning and plasma treatment of the substrate; Step 2, using a metal target and a ceramic target as co-sputtering targets, magnetron sputtering co-deposit a metal nanowire array-ceramic composite film on a substrate; Step 3, immersing the composite material in a chemical etching solution A, etching and then washing to obtain a solid nanopore array template; Step 4, immersing the solid nanopore array template in a chemical etching solution B at 15-35° C. and etching for 1-15 min to adjust the pore size, and washing to obtain the solid nanopore array template after pore size adjustment; The pore size regulation refers to the change of the diameter of the nanopores in the solid-state nanopore array template to 0.1-1.2 nm; The chemical etching solution A is an aqueous solution of NH3·H2O and / or H2O2, and the molar fraction of the solute in the aqueous solution is 0.3-1 mol / L; The chemical etching solution B is an aqueous solution of one or more of NaOH, KOH, HCl, and H2SO4, and the molar fraction of the solute in the aqueous solution is 0.01-1 mol / L.
2. The method for controlling pore size of a solid-state nanopore array template according to claim 1, characterized in that: The substrate includes one or more of a single crystal silicon wafer, a quartz glass wafer, a sapphire, a flexible PET and an Al foil; In step 1, the ultrasonic treatment includes treatment with one or more solutions of acetone, ethanol, and deionized water for 10-30 min; the plasma treatment is carried out at 5-20×10 -5 Pa deposition pressure for 5-20 min.
3. The method for controlling pore size of a solid-state nanopore array template according to claim 1, characterized in that: The diameter of the nanopores in the solid-state nanopore array template is 1-10 nm, the average spacing of the nanopores is 3-20 nm, and the array period is 6-40 nm.
4. The method for controlling pore size of a solid-state nanopore array template according to claim 1, characterized in that: The metal phase filling rate in the composite film is 5-30%, and the ceramic phase volume accounts for 70-95%.
5. The method for controlling pore size of a solid-state nanopore array template according to claim 1, characterized in that: The metal target material includes one or more of Ag target, Cu target and Al target; the ceramic target material includes one or more of Al2O3, AlN and SiO2.
6. The method for controlling pore size of a solid-state nanopore array template according to claim 1, characterized in that: In step 2, during magnetron sputtering, the sputtering power of the metal target is 10-20 W, the sputtering power of the ceramic target is 60-100 W, and the pre-deposition pressure is 5-10×10 -5 Pa.
7. The method for controlling pore size of a solid-state nanopore array template according to claim 1, characterized in that: In step 3, the etching temperature is 15-35° C., and the etching time is 1-6 h.
8. The method for controlling pore size of a solid-state nanopore array template according to claim 1, characterized in that: The thickness of the nanopore layer in the solid-state nanopore array film is 10-300 nm.
9. The method for controlling pore size of a solid-state nanopore array template according to claim 1, characterized in that: The porosity of the solid-state nanopore array template is 7%-64%.
10. The method for controlling pore size of a solid-state nanopore array template according to claim 1, characterized in that: The method also includes repeating step 4 to adjust the pore size of the nanopore so that the diameter change is greater than 1.2 nm.
Citation Information
Patent Citations
Biomolecule distinguishing method and solid-state nanopore four-hole array device thereof
CN115093948A
Method for preparing Si nanopore array template with independently adjustable pore pitch and pore diameter
CN101949017A
Preparation method of metal / non-metal composite film of vertical array structure
CN107740058A
Large-scale plasmonic hybrid framework with built-in nanohole arrays as multifunctional optical sensing platforms
US20230047636A1
Superhydrophobic diamond-like composite layer structure and preparation method therefor
WO2020119510A1
